Tensile behavior and load transfer mechanism of concrete-filled square steel tube exterior-diaphragm connections stiffened with PBL. (15th March 2021) - Zhu, Weiqing; Mo, Zhipeng; Liu, Yongjian; Cui, Yue
Highlights: CFSST exterior-diaphragm connections stiffed with PBL were tested under tensile load. Tensile behavior and load transfer mechanism of different connections were compared. CFSST exterior-diaphragm connections stiffened with PBL had good tensile behavior. The failure of the innovative connections behaved as the yielding of branch plates. PBL relieved the stress concentration at the column corners. Abstract: An innovative concrete-filled square steel tube (CFSST) exterior-diaphragm connection stiffened with perfobond ribs (PBL) is proposed to overcome the limits of CFSST exterior-diaphragm connections. Different CFSST connections, including one ordinary CFSST connection, one CFSST exterior-diaphragm connection, two CFSST exterior-diaphragm connections stiffened with PBL, and two CFSST connections stiffened with PBL, were tested under tensile loads. The tensile behavior, including failure modes, initial stiffness, yield load, peak load, and deformation of different connections, was analyzed and compared based on the test results. By analyzing the stress distribution in critical sections of branch plates or exterior diaphragms and the contribution of different parts to the total tensile load in critical sections of joint regions at different loading stages using the finite element method, the load transfer mechanism of different connections was analyzed and compared quantitatively. The results showed that the PBL transferred a considerable percentage of the tensile load from the branch plates or exterior diaphragms to the core concrete, which resulted in a more uniform stress distribution in the branch plates and exterior diaphragms and caused the core concrete to have a direct function in the load transfer in joint regions; thus, the load transfer and deformation condition of connections were improved. The innovative CFSST exterior-diaphragm connections stiffened with PBL had excellent tensile behavior with the largest initial stiffness, yield load, and peak load, the smallest joint region deformation, and the most uniform stress distribution, thus failed due to the yielding of branch plates.